Nanocrystalline particle coatings on a-alumina powders by a carbonate precipitation and thermal-assisted combustion route - Kim, Sang Woo; Jung, Young Mi (AMER SCIENTIFIC PUBLISHERS, 2007)
We have suggested ultrafine particle coating processes for preparing nanocrystalline particle coated a-alumina powders by a carbonate precipitation and thermal-assisted combustion route, which is environmentally friendly. The nanometric ammonium aluminum carbonate hydroxide (AACH) as a precursor for coating of alumina was produced from precipitation reaction of ammonium aluminum sulfate and ammonium hydrogen carbonate. The synthetic crystalline size and morphology were greatly dependent on pH and temperature. By adding ammonium aluminum sulfate solution dispersed the a-alumina core particle in the ammonium hydrogen carbonate aqueous solution, nanometric AACH with a size of 5 nm was tightly bonded and uniformly coated on the core powder due to formation of surface complexes by the adsorption of carbonates, hydroxyl and ammonia groups on the surface of aluminum oxide. The synthetic precursor rapidly converted to amorphous- and gamma-alumina phase without significant change in the morphological features through decomposition of surface complexes and thermal-assisted phase transformation. As a result, the nanocrystallirie polymorphic particle coated a-alumina core powders with highly uniform distribution were prepared from the route of carbonate precipitation and thermal-assisted combustion.
Keywords: SOLID-STATE NMR; PHYSICOCHEMICAL PROPERTIES; HYDROXIDES; FTIR